MISR photogrammetric data reduction for geophysical retrievals - Jovanovic, V.M.; Smyth, M.M.; Jia Zong; Ando, R.; Bothwell, G.W. (IEEE transactions on geoscience and remote sensing, 1998)
The theoretical concept, based on modern photogrammetric methods, underlying the design of the Multi-angle Imaging SpectroRadiometer (MISR) science data processing system, responsible for the autonomous and continuous georectification of multiangle imagery, is the subject of this paper. The algorithm partitions effort between the MISR Science Computing Facility and the Earth Observing System (EOS) Distributed Active Archive Center (DAAC) in a way that minimizes the amount of processing required at the latter location to rectify and map project remotely sensed data online, as it comes from the instrument. The algorithm deals with the following issues: (1) removal of the errors introduced by inaccurate navigation and attitude data; (2) removal of the distortions introduced by surface topography; (3) attainment of a balance between limited hardware resources, huge data volume and processing requirements, and autonomous and nonstop aspects of the production system.